Vibrational coherence transfer in the ultrafast intersystem crossing of a diplatinum complex in solution - Monni, Roberto; Capano, Gloria; Auböck, Gerald; Gray, Harry B; Vlček, Antonín; Tavernelli, Ivano; Chergui, Majed (Proceedings of the National Academy of Sciences - PNAS, 2018)
We investigate the ultrafast transient absorption response of tetrakis(μ-pyrophosphito)diplatinate(II), [Pt (μ-P O H ) ] [hereafter abbreviated Pt(pop)], in acetonitrile upon excitation of its lowest singlet A state. Compared with previously reported solvents [van der Veen RM, Cannizzo A, van Mourik F, Vlček A, Jr, Chergui M (2011) 133:305-315], a significant shortening of the intersystem crossing (ISC) time (<1 ps) from the lowest singlet to the lowest triplet state is found, allowing for a transfer of vibrational coherence, observed in the course of an ISC in a polyatomic molecule in solution. Density functional theory (DFT) quantum mechanical/molecular mechanical (QM/MM) simulations of Pt(pop) in acetonitrile and ethanol show that high-lying, mostly triplet, states are strongly mixed and shifted to lower energies due to interactions with the solvent, providing an intermediate state (or manifold of states) for the ISC. This suggests that the larger the solvation energies of the intermediate state(s), the shorter the ISC time. Because the latter is smaller than the pure dephasing time of the vibrational wave packet, coherence is conserved during the spin transition. These results underscore the crucial role of the solvent in directing pathways of intramolecular energy flow.